(untitled) (PHARMACON, 2013)
Abelmoschus manihot L. has been used traditionally as folks medicine plant and it contain flavonoid and steroid that has health benefit. The objectives of this research were to determine anti obesity and hypolipidemic activity of flavonoid and steroid extract from Abelmoschus manihot L. on white male Wistar induced with high content of protein and lipid food. Anti obesity test were evaluated by the decreasing of rats weight, whereas hypolipidemic test were evaluated by the decreasing of total cholesterol levels photometrically using Liebermann-Burchard method. The rats were divided into four groups, namely the negative control (distilled water), extract treatment groups (flavonoids and steroids), and a positive control group (simvastatin). The percentations of Weight reducing and cholesterol level were analyzed by ANOVA, if there were significant in groups, it continued with Duncan Multiple Range Test. The results showed that treatment group posses anti obesity activity, whereas flavonoid extract decrease 7.85% body weight of rats and steroids extract were 13.70% of body weight. Flavonoids showed hypolipidemic effects by decrease rats cholesterol levels by 86.45% and steroid extract decrease cholesterol levels by 72.53%. Keywords : Abelmoschus manihot L., flavonoid extract, steroid extract, anti obesity, hypolipidemic